PENGARUH UANG JAPUIK TERHADAP PEWARISAN PADA MASYARAKAT DESA KALAWI, KECAMATAN SUNGAI GERINGGING, PADANG PARIAMAN, SUMATERA BARAT: The Influence Of Japuik Money On Inheritance In The Community Of Kalawi Village, Sungai Geringging Sub-District, Padang Pariaman, West Sumatra - Karmilah; Khairani Bakri (Reformasi Hukum Trisakti, 2024)
The Bajapuik (Jemput) tradition and Japuik money are characteristic or identity of the Pariaman community, especially Kalawi Village. Bajapuik is considered an obligation where the wife's family gives the husband (future husband) a sum of money or value according to mutual agreement before the marriage contract. The formulation of the problem in this article is how is the concept of japuik money in the Kalawi Village community, Sungai Geringging, Padang Pariaman, West Sumatra? and Does japuik money affect the inheritance of the residents of Kalawi Village, Sungai Geringing, Padang Pariaman, West Sumatra? The research method is Social law, descriptive analytical using primary and secondary data, data collection in the form of interviews and literature studies, qualitative data analysis with deductive conclusions. Japuik money is a gift from the bride and is returned and there is an addition from the groom to the bride. The determination of japuik money is carried out during the maresek event and together with the determination of other needs. While the gift is given when accompanying the groom to celebrate the wedding at his wife's house. The prospective groom will return japuk money in form of a gift in form of gold/silver of the same/greater value.